Expansion of Human Regulatory T-Cells From Patients With Type 1 Diabetes - Putnam, Amy L.; Brusko, Todd M.; Lee, Michael R.; Liu, Weihong; Szot, Gregory L.; Ghosh, Taumoha; Atkinson, Mark A.; Bluestone, Jeffrey A. (Diabetes (New York, N.Y.), 2009)
Expansion of Human Regulatory T-Cells From Patients With Type 1 Diabetes Amy L. Putnam 1 , Todd M. Brusko 1 , Michael R. Lee 1 , Weihong Liu 1 , Gregory L. Szot 1 , Taumoha Ghosh 1 , Mark A. Atkinson 2 and Jeffrey A. Bluestone 1 1 Diabetes Center at the University of California, San Francisco (UCSF), San Francisco, California 2 Department of Pathology, University of Florida, College of Medicine, Gainesville, Florida Corresponding author: Jeffrey A. Bluestone, jbluestatdiabetes.ucsf.edu Abstract OBJECTIVE— Regulatory T-cells (Tregs) have catalyzed the field of immune regulation. However, translating Treg-based therapies from animal models of autoimmunity to human clinical trials requires robust methods for the isolation and expansion of these cells—a need forming the basis for these studies. RESEARCH DESIGN AND METHODS— Tregs from recent-onset type 1 diabetic patients and healthy control subjects were isolated by fluorescence-activated cell sorting and compared for their capacity to expand in vitro in response to anti-CD3–anti-CD28–coated microbeads and IL-2. Expanded cells were examined for suppressive function, lineage markers and FOXP3, and cytokine production. RESULTS— Both CD4 + CD127 lo/− and CD4 + CD127 lo/− CD25 + T-cells could be expanded and used as Tregs. However, expansion of CD4 + CD127 lo/− cells required the addition of rapamycin to maintain lineage purity. In contrast, expansion of CD4 + CD127 lo/− CD25 + T-cells, especially the CD45RA + subset, resulted in high yield, functional Tregs that maintained higher FOXP3 expression in the absence of rapamycin. Tregs from type 1 diabetic patients and control subjects expanded similarly and were equally capable of suppressing T-cell proliferation. Regulatory cytokines were produced by Tregs after culture; however, a portion of FOXP3 + cells were capable of producing interferon (IFN)-γ after reactivation. IFN-γ production was observed from both CD45RO + and CD45RA + Treg populations. CONCLUSIONS— The results support the feasibility of isolating Tregs for in vitro expansion. Based on expansion capacity, FOXP3 stability, and functional properties, the CD4 + CD127 lo/− CD25 + T-cells represent a viable cell population for cellular therapy in this autoimmune disease. Footnotes Published ahead of print at http://diabetes.diabetesjournals.org on 15 December 2008. A.L.P. and T.M.B. contributed equally to this work. Readers may use this article as long as the work is properly cited, the use is educational and not for profit, and the work is not altered. See http://creativecommons.org/licenses/by-nc-nd/3.0/ for details. The costs of publication of this article were defrayed in part by the payment of page charges. This article must therefore be hereby marked “advertisement” in accordance with 18 U.S.C. Section 1734 solely to indicate this fact. Accepted December 5, 2008. Received August 25, 2008. DIABETES